Brain doping: stimulants use and misuse among a sample of Italian college students - Majori, S. (J Prev Med Hyg, 2017)
INTRODUCTION. The non-medical use of prescription stimulants (NMUPS) has become the subject of great interest for its diffusion among university students, who abuse these substances to cope with the increasing load of academic stress. NMUPS has been widely investigated in the U.S. due to its increasing trend; this behavior, however, has also been reported in Europe. The aim of this cross-sectional study was to examine stimulants misuse in a Northern Italian geographic area, identifying possible developments of the phenomenon in Italy. METHODS. To evaluate academic and extra-academic NMUPS (Methylphenidate and Amphetamines), an anonymous multiplechoice questionnaire was administrated to a sample of Bachelor's and Master's degrees students attending a University North East of Italy. Data elaboration and CI 95% were performed with Excel software 2013. Fisher's exact tests were performed using Graph- Pad INSTAT software. RESULTS. Data from 899 correctly completed questionnaires were analyzed in this study. 11.3% of students reported NMUPS, with an apparent greater use by students aged 18-22 years (73.5%) and without any statistically significant gender predominance. Fifty-seven point eight percent of students used stimulants at most five times in six months, and the most frequent academic and extra-academic reasons to use them were respectively to improve concentration while studying (51.0%) and sports performance (25.5%). NMUPS was higher among working students than nonworking ones (p < 0.05), suggesting a use of stimulants to cope with stress by the first ones. CONCLUSIONS. These exploratory and preliminary data suggest that NMUPS is quite relevant in Northern Italy, suggesting a need for preventive and monitoring measures, as well as future analysis via a longitudinal multicenter study.